Critical thinking profile of students in solving mathematics problems through STEM learning model - S Retnowati; R Riyadi; S Subanti (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The 21st century fosters competition and challenges in various fields, including education. Various efforts have been made to improve the education quality in Indonesia; one of them is the implementation of education based on Science, Technology, Engineering, and Mathematics (STEM). Critical thinking is also an important thing for success in the 21st century. This study aims to describe the critical thinking profile of students in solving mathematics problems through STEM learning. The method is qualitative research. The subjects are three students with high, medium, and low ability. Test, interview, and documentation are employed as the technique of collecting data. The results reveal that the high-ability student is able to achieve all aspects of critical thinking and she actively participates in learning and teaching activities through the STEM learning model. The medium-ability student only fulfils a number of aspects. Meanwhile, the low-ability student can only fulfil the interpretation aspect and she does not actively participate in the learning process. The results are supported by the interview result with the students. They state that STEM learning is fun, give them an opportunity to think critically and facilitate them in understanding the lesson easily.